1992
DOI: 10.1246/bcsj.65.2624
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties, and Crystal Structures of a Series of Dinuclear Manganese(III) Complexes with 1,5-Bis(salicylideneamino)-3-pentanol and Various Anions: Formation of a Tetranuclear Manganese(III) Complex

Abstract: μ-Alkoxo-bridged dinuclear and tetranuclear manganese(III) complexes with 1,5-bis(salicylideneamino)-3-pentanol (H3L), [Mn2(L)(CH3O)Cl2(CH3OH)2] (1), [Mn2(L)(CH3O)(CH3COO)(CH3OH)2]X (X = Br (2), I (3)), [Mn2(L)(CH3O)(CH3COO)(CH3OH)Y] (Y = NCS (4), N3 (5), ClO4 (6)), [Mn2(L)(CH3O)(NCO)2(H2O)2] (7), and [Mn4(L)2(O)2(CH3COO)2]·4H2O·2CH3OH (8) have been prepared and characterized by infrared and electronic spectra, magnetic susceptibilities, and cyclic voltammetry. The molecular structures of 1–5, 7, and 8 were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…3) was obtained with the following parameters: J = À13.1 cm À1 , g = 1.90 and p = 0.2%. The calculated exchange parameter J falls in the range observed for other dialkoxo bridged diMn III complexes with short MnÁ Á ÁMn distances (2.98-3.00 Å ) [18,19,27,[34][35][36][37] that allow direct overlap between the d xy orbitals.…”
Section: Magnetic Propertiesmentioning
confidence: 55%
“…3) was obtained with the following parameters: J = À13.1 cm À1 , g = 1.90 and p = 0.2%. The calculated exchange parameter J falls in the range observed for other dialkoxo bridged diMn III complexes with short MnÁ Á ÁMn distances (2.98-3.00 Å ) [18,19,27,[34][35][36][37] that allow direct overlap between the d xy orbitals.…”
Section: Magnetic Propertiesmentioning
confidence: 55%
“…The presence of two non-parallel Jahn-Teller axes is a very unusual structural feature for dinuclear Mn III complexes where a parallel orientation has been observed for a number of complexes related to 2 [27][28][29]. However, a similar type of Jahn-Teller axes orientation was reported for the tetranuclear complex [Mn 4 (L(O) 2 OAc) 2 ] AE 4H 2 O AE MeOH (where LH 2 = 1,5-bis(salisylideneamino)-3-pentanol) [30]. Calculating the least squares planes for the equatorial O 3 N donor set on respective metal atom shows that the equatorial coordination around Mn1 is more distorted than that around Mn2.…”
mentioning
confidence: 65%
“…The elucidation of the crystal structures of oxygen-evolving photosystem II from Thermosynechococcus elongatus at 3.8 Å resolution by Zouni et al [5] and Thermosynechococcus vulcanus at 3.7 Å resolution by Kamiya and Shen [6], respectively, indicated that a tetranuclear manganese center is at the heart of the water splitting reaction, triggered efforts toward the synthesis of structural and functional analogues of the oxygen-evolving complex. The three general classes of tetranuclear manganese complexes with variable oxidation states which are synthesized are (i) the [Mn 4 (l 3 -O) 2 ] core using the carboxylate aggregate developed by Christou and Hendrickson [7][8][9] (ii) the [Mn 4 (L) 2 (O) 2 (CH 3 COO) 2 ] core where L = the schiff base ligands 2,6-bis(salicylideneaminomethyl)-4-methylphenol or 1,5-bis-(salicylideneamino)-3-pentanol or 2,6-bis(N-(4-imidazolylethyl)iminomethyl]-4-methylphenol reported by Mikuriya et al [10][11][12][13] and (iii) the inorganic analogues of M 2+ (12-crown-4) such as Mn(II)[Mn(III)-salicylhydroximate] 4 described by Pecoraro et al [14,15] In all the above cases the Mn 4 (III) aggregate is formed with the participation of ancillary bridging ligands such as acetato-, benzoato-, etc. Herein we report the X-ray structure of a neutral tetranuclear Mn(III) cluster containing The article was accepted and intended for the Special issue but was left out due to a production error.…”
Section: Introductionmentioning
confidence: 99%